2023
DOI: 10.1136/bmjopen-2022-069051
|View full text |Cite
|
Sign up to set email alerts
|

What learning strategies are commonly used by hospital pharmacists in the process of self-directed learning? A multicentre qualitative study

Abstract: ObjectiveAs lifelong learners, hospital pharmacists must continually improve their self-directed learning skills. Reasonable learning strategies have been proven to enhance self-directed learning (SDL) significantly. Therefore, this study aims to investigate the SDL strategies used by hospital pharmacists in depth to provide them with a reference for the development of their SDL skills.SettingThe study was conducted in three tertiary hospitals in Henan, China.Design and participantsThis study employed a multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…With the advancement of technology and the development of society, the rational use of learning resources through multiple ways is an effective strategy to enhance SDL competence [25]. In a previous study conducted by our group, the ndings revealed SDL-related learning strategies frequently used by hospital pharmacists, including four aspects: use of information resources, application of cognitive strategies, making learning plans and use of learning platforms [12]. It is worth pointing out that other studies have mentioned a decreasing trend in students' SDL ability as the school year progresses [21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the advancement of technology and the development of society, the rational use of learning resources through multiple ways is an effective strategy to enhance SDL competence [25]. In a previous study conducted by our group, the ndings revealed SDL-related learning strategies frequently used by hospital pharmacists, including four aspects: use of information resources, application of cognitive strategies, making learning plans and use of learning platforms [12]. It is worth pointing out that other studies have mentioned a decreasing trend in students' SDL ability as the school year progresses [21].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of this study, in which participants emphasized the learning atmosphere created by peers, colleagues, and other people around them, and mentioned that SDL could be improved through teamwork. In addition, participants in this study suggested other SDL improvement based on their own personal experiences, including adjusting the mindset, setting goals, learning to selfevaluate, and making rational use of learning resources [12]. With the advancement of technology and the development of society, the rational use of learning resources through multiple ways is an effective strategy to enhance SDL competence [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations